Pengaruh Work Life Balance dan Perceived Organizational Support (POS) terhadap Employee Performance dengan Job Satisfaction sebagai Variabel Intervening (Studi pada Pegawai UPTD Puskesmas di Kabupaten Grobogan) - Okka Dzakira; Lutfi Nurcholis (ARZUSIN, 2026)
This study was motivated by the imbalance between work and personal life and the suboptimal level of organizational support, which affected employee job satisfaction and performance. This study aimed to analyze the effect of work-life balance and perceived organizational support on employee performance, with job satisfaction as an intervening variable. This study used a quantitative approach with an explanatory research design. Data were collected through questionnaires administered to 112 ASN and non-ASN employees at the Tawangharjo and Wirosari Community Health Center Technical Implementation Units, Grobogan Regency, who were selected using purposive sampling. Data were analyzed using Partial Least Squares (PLS) with the assistance of SmartPLS. The results showed that work-life balance and perceived organizational support had a direct negative effect on employee performance, but both had a positive and significant effect on performance through the mediation of job satisfaction. These findings confirm that job satisfaction serves as an intervening mechanism that bridges the effect of work-life balance and organizational support on improving employee performance. The conclusion of this study indicates that improving employee performance is determined not only directly by organizational factors but also by employees’ psychological conditions, particularly job satisfaction. The implications of this study emphasize the importance of organizations formulating policies that support work-life balance, strengthen organizational support, and improve job satisfaction in order to enhance employee performance in public health services.